Ketidak Hati-Hatian Penggunaan Media Sosial Yang Menyebabkan Tindak Pidana Pencemaran Nama Baik - Salsa Bila Juita (Ethics and Law Journal: Business and Notary, 2024)
Actions that harm a person's reputation or good name by spreading negative, slanderous or insulting information. The purpose of this research is to study and discuss law enforcement for perpetrators of slander and find out the factors that cause someone to commit acts that can harm the dignity of other people. The method of approach is normative juridical, which is an approach in legal research that focuses on the analysis of applicable legal norms. This method focuses on understanding and interpreting legal norms. Meanwhile, the data collection technique is literature study, namely collecting, reviewing and analyzing literature or library materials that are relevant to the topic or problem of this research. The results of this research will later discuss government resolution methods and government regulations to uphold justice for issues raised with sanctions appropriate to existing regulations, then discuss the factors that cause someone to have the heart to slander other people and efforts to ensure that these actions can be achieved. minimized so that people can be more careful and wise when using services on social media. Keywords: negative information, detrimental, justice